Historical and cultural variations of teeth aesthetics - Fernandez-Montecinos, Enrique Alberto; Padilla-Alvear, Paula Andrea (Revista Facultad de Odontología Universidad de Antioquia, 2022)
Dental aesthetics is a topic of wide relevance in current dentistry, both in dental education and in private practice. When people express that they want a beautiful smile, both dentists and patients think of whitening tooth color. What is the reason for this tacit agreement? Some might argue that a healthy smile is naturally whiter, but we know that physiological functionality is not always associated with socially determined aesthetics. Furthermore, some aesthetics procedures might involve body modifications that are not necessarily natural nor healthy. The aim of this review is to to provide elements of discussion about historical and cultural aspects related to the positioning of tooth color as an important part of an aesthetic ideal. To argue that the desire for whiter teeth resides in cultural influences. To invite reflection if "white teeth" should be equated with "healthy teeth", with the consequences this assumption would imply in our professional field.